A STUDY OF LONGING AND SACRIFICE IN WILLA CATHER'S ON THE GULL'S ROAD - Nuristama, Ramadhina Ulfa (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This study focuses on the themes of longing and sacrifice in Willa Cather's On the Gull's Road. The objective of this study is to examine how the narrator and Alexandra represent these themes in the story. New Criticism theory is applied to explore how the themes of longing and sacrifice are developed through the main characters. This study employs close reading as a method to analyze relevant passages that illustrate the emotional and relational dynamics between the narrator and Alexandra. The analysis uncovers how Cather portrays the complex feelings of desire and restraint within the story by paying careful attention to language, imagery, and narrative structure. The results show that Cather effectively conveys the narrator's longing for Alexandra through his introspective reflections and vivid descriptions of their interactions. Alexandra's character embodies sacrifice as she navigates her commitment to her husband and her growing connection with the narrator. This study concludes that Cather's portrayal of longing and sacrifice enriches the story's emotional depth, highlighting the delicate balance between personal desires and societal constraints. This insightful description of the main characters' emotional difficulties provides readers with an advancing examination of human connections and the complexity of love and obligation.